The effect of androgen blockade on [68Ga]Ga-PSMA-11 and [18F]FDG PET uptake in patients with recurrent or metastatic salivary duct carcinoma: a prospective imaging study - Niels J. van Ruitenbeek; Maike J. M. Uijen; Chantal M. L. Driessen; Maartje C. van Rijk; Steffie M. B. Peters; Bastiaan M. Privé; Gerald W. Verhaegh; Adriana C. H. van Engen-van Grunsven; Martin Gotthardt; James Nagarajah; Carla M. L. van Herpen (EJNMMI Research)
Abstract Background The expression of prostate-specific membrane antigen (PSMA), a target for oncological imaging and treatment, is upregulated by androgen blockade in prostate cancer. Salivary duct carcinoma (SDC), an aggressive histological subtype of salivary gland cancer, resembles prostate cancer in terms of PSMA and androgen receptor (AR) expression. A similar upregulation of PSMA in SDC would have implications for future studies with PSMA-targeted imaging and therapy. Additionally, FDG PET/CT scans are frequently used for SDC imaging, but the effect of androgen blockade on FDG uptake is unknown. This study investigated the effect of combined androgen blockade (CAB) on tumour PSMA and FDG uptake in patients with SDC. Results Eight patients with recurrent and/or metastatic AR-positive SDC who started CAB (goserelin plus bicalutamide) as standard of care were prospectively enrolled. [68 Ga]Ga-PSMA-11 and [18F]FDG PET/CT scans were performed within 21 days before and 21 ± 7 days after CAB initiation. PET parameters, including SUVmax, were obtained for PSMA and FDG positive lesions. A total of 80 metastatic lesions were analysed on a per-lesion basis. SUVmax changes after CAB initiation were categorised as increased (≥ + 20%), stable (between -20% and + 20%), or decreased (≤ -20%). The PSMA SUVmax increased in 20 lesions (25%), remained stable in 46 lesions (58%), and decreased in 14 lesions (18%), with no significant overall change (Wilcoxon signed rank test, p = 0.74). The FDG SUVmax increased in 35 lesions (44%), remained stable in 39 lesions (49%), and decreased in 6 lesions (8%), with a significant overall median increase of + 0.97 (Wilcoxon signed rank test, p < 0.001). The median PFS was 2.2 months (95% confidence interval 1.7–2.7 months). Conclusions Androgen blockade in patients with recurrent and/or metastatic SDC did not induce a significant increase in tumour PSMA uptake after three weeks. In contrast, tumour FDG uptake increased significantly after three weeks of CAB, which may reflect the poor tumour response in this cohort and/or a transient treatment-related effect. Trial registration: ClinicalTrials.gov, NCT04214353. Registered 13 December 2019.